Financing Future Feed-in Electricity Tariffs from Currently Installed RES-E Generating Capacity - Pereira, Alfredo Marvão; Pereira, Rui Marvão (Archives of Business Research, 2021)
This paper addresses the issue of financing the excess costs of electricity generation from currently installed renewable energy production capacity. We use a dynamic computable general equilibrium model of the Portuguese economy. We consider three issues: the effects of the excess-costs; the effects of annuitizing the costs; and, the effects of different financing mechanisms. Following the logic of the tariff deficit, we recommend the annuitizing of these excess costs. This strategy is justified on distributional grounds. We also find that financing through carbon taxation is a better alternative than passing these excess costs to electricity consumers in the form of higher future prices. This is consistent with the idea that renewable production is not an issue pertaining to the electricity market but rather a part of the national quest for decarbonization. Finally, we show that there is little reason to extend such preferential financing to future renewable capacity installation.